Literature and the Polities of Family in Seventeenth-Century England - Su Fang, Ng (Cambridge University Press, 2013)
In 1615 James I ordered the publication of God and the King, which supported the obligation to take the oath of allegiance: the work announces itself to be “Imprinted by hisMaiesties speciall priuiledge and command.”1 Attributed to Richard Mocket, at the time warden of All Souls, Oxford, the pamphlet defends divine right absolutism by making the patriarchal analogy linking father and king. Cast in the form of a dialogue, God and the King wastes little time in preliminaries. After a brief greeting, Philalethes, just come from a catechism, launches into a justification of monarchical authority by way of the fifth commandment. A good cathechumen, he recites the lesson that the names of father and mother include all other authorities, especially royal authority